FISHER INFORMATION MATRIX FOR CROVELLI’S AND GAMMA BETA II BIVARIATE DISTRIBUTIONS - SILVA, Ana Paula Coelho Madeira; DINIZ, Adélia Conceição (Brazilian Journal of Biometrics, 2021)
In this paper, a system of nonlinear equations for the maximum likelihood estimators as wel as the exact forms of the Fisher information matrix for Crovelli’s bivariate gamma distribution and bivariate gamma beta distribution of the second kind are determined. An application of the results to the rainfall data from the city of Passo Fundo are provided.